Os sistemas de treinamento de força pirâmide crescente e drop-set não promovem maiores ganhos de força, massa muscular e mudanças na arquitetura muscular comparado ao treinamento de força tradicional em homens treinados - Angleri, Vitor (Universidade Federal de São Carlos, 2017)
Purpose The aim of this study was to compare the effects of crescent pyramid (CP) and Drop-set (DS) systems with traditional resistance training (TRAD) with equalized total training volume (TTV) on maximum dynamic strength (1-RM), muscle cross-sectional area (CSA), pennation angle (PA) and fascicle length (FL). Methods Thirty-two volunteers had their legs randomized in a within-subject design in TRAD (3-5 sets of 6-12 repetitions at 75% 1-RM), CP (3-5 sets of 6-15 repetitions at 65-85% 1-RM) and DS (3-5 sets of ~50-75% 1-RM to muscle failure) protocols. Each leg was trained for 12 weeks. Participants had one leg fixed in the TRAD while the contralateral leg performed either CP or DS to allow for TTV equalization. Results The CSA increased significantly and similarly for all protocols (TRAD: 7.6%; CP: 7.5%; DS: 7.8%). All protocols showed significant and similar increases in leg press 45º (TRAD = 25.9%; CP = 25.9%; DS = 24.9%) and leg extension 1-RM loads (TRAD = 16.6%; CP = 16.4%; DS = 17.1%). All protocols increased PA (TRAD = 10.6%; CP = 11.0%; DS = 10.3%) and FL (TRAD = 8.9%; CP = 8.9%; DS = 9.1%) similarly. Conclusion CP and DS systems do not promote greater gains in strength muscle hypertrophy and changes in muscle architecture compared to traditional resistance training.
Crescent pyramid and drop-set systems do not promote greater strength gains, muscle hypertrophy, and changes on muscle architecture compared with traditional resistance training in welltrained men
Keywords: Treinamento de força; Volume total; Área de Secção Transversa Muscular; Força muscular; Ângulo de penação; Comprimento do fascículo; CIENCIAS DA SAUDE::EDUCACAO FISICA